Let
f ( n ) = i = 1 ∏ n ( 1 − ( i + 1 ) 2 1 )
Determine f ( 1 9 9 9 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Excellent work Tasmeem!
i thought it ws telescopic series i did till 4th step but i cannot go further
Thank you for sharing this problem
Excellent..I really appreciate your solutions and their clarity :)
Thanks! Really good
Try the product for the first few terms. You will notice that the result is f ( n ) = 2 ( n + 1 ) n + 2 . Hence exact answer is 2001/4000.
We'll show that f(n) = (n+2)/(2(n+1)) and then let n = 1999 to get our answer of 0.50025.
First let's look at a single factor of our product series: (1 - 1/(i+1)^2) = ((i+1)^2 - 1)/(i+1)^2 = (i(i+2))/(i+1)^2 .
Now let's have a look at what our product series looks like with this substitution : f(n) = ((1(3))/(2^2)) ((2(4))/3^2) ... (((n-1)(n+1))/n^2) ((n(n+2))/(n+1)^2) = (n! * ((n+2)!)/2)/(n+1)!^2 =1/2 * n!/(n+1)! * (n+2)!/(n+1)! = 1/2* 1/(n+1) * (n+2) = (n+2)/(2(n+1)).
Plugging in 1999 into f(n), we have : f(1999) = (2001)/(2*(2000)) = 0.50025.
did the same way.
It's very interesting that f(n) has the form (1/2) GAMMA(n+1.) GAMMA(n+3.)/GAMMA(n+2.)^2
Let there be k terms .The answer is [{(k/2)+1}/k+1]
After rewriting the difference of squares as ( n + 1 n + 2 ) ( n + 1 n ) we evaluate the first terms getting this:
( 2 3 ) ( 2 1 ) ( 3 4 ) ( 3 2 ) ( 4 5 ) ( 4 3 ) … .
The idea is to note that for an specific n , the only terms that will not cancel are 2 1 and the penultimate term (excepting n = 1 , case in which both terms don't cancels). So for the case n = 1 9 9 9 we're left with the terms ( 2 1 ) ( 2 0 0 0 2 0 0 1 ) . Finally,
f ( 1 9 9 9 ) = 4 0 0 0 2 0 0 1 = 0 . 5 0 0 2 5 .
Problem Loading...
Note Loading...
Set Loading...
t h e g i v e n e q u a t i o n i s f ( n ) = i = 1 ∏ n ( 1 − ( i + 1 ) 2 1 )
N o w , f ( 1 9 9 9 ) = i = 1 ∏ 1 9 9 9 ( 1 − ( i + 1 ) 2 1 ) = i = 1 ∏ 1 9 9 9 ( ( i + 1 ) 2 ( i + 1 ) 2 − 1 ) = i = 1 ∏ 1 9 9 9 ( ( i + 1 ) 2 i 2 + 2 i ) = i = 1 ∏ 1 9 9 9 ( ( i + 1 ) 2 i ( i + 2 ) ) = i = 1 ∏ 1 9 9 9 ( i + 1 i × i + 1 i + 2 ) = i = 1 ∏ 1 9 9 9 ( i + 1 i ) × i = 1 ∏ 1 9 9 9 ( i + 1 i + 2 )
n o w , t h e f i r s t t e r m , i = 1 ∏ 1 9 9 9 ( i + 1 i ) = 2 1 × 3 2 × 4 3 × . . . × 1 9 9 9 1 9 9 8 × 2 0 0 0 1 9 9 9 = 2 0 0 0 1 [ B e c u a s e e a c h t e r m t e l e s c o p e s ]
a g a i n , t h e s e c o n d t e r m , i = 1 ∏ 1 9 9 9 ( i + 1 i + 2 ) = 2 3 × 3 4 × 4 5 × . . . × 1 9 9 9 2 0 0 0 × 2 0 0 0 2 0 0 1 = 2 2 0 0 1 [ B e c u a s e e a c h t e r m t e l e s c o p e s ]
T h u s w e g e t , i = 1 ∏ 1 9 9 9 ( i + 1 i ) × i = 1 ∏ 1 9 9 9 ( i + 1 i + 2 ) = 2 0 0 0 1 × 2 2 0 0 1 = 4 0 0 0 2 0 0 1 = 0 . 5 0 0 2 5